Transformasi Pendidikan Agama dan Sains Dikotomik ke Pendidikan Nondikotomik - Maksudin, Maksudin; Maksudin (Jurnal Pendidikan Islam, 2015)
Modern society is experiencing a spiritual emptiness that caused by dichotomous thinkingbetween religion and science. Therefore, it is important to do the transformation fromdichotomous understanding and education into nondichotomous. This effort can beused as an alternative to solve the problems of the education system and the dichotomouslife system. Some of the advantages of nondichotomous for education system and thelife system is the realization of: integration, interconnection, holistic, integrated,comprehensive, one system, one entity, strong, collective, religious, humane, peaceful,familiar, humble, thorough, work hard, work smartly, work well, work completely, andwork sincerely. While the weaknesses of the dichotomy in the life of the nation leadto several things: separation, stand-alone, partial, incomplete, divided, fragmented,dispersed, collapsed, weak, individual, secular, radical, anarchist, haughty, arrogant,incomplete, fast lackluster, quickly surrendered, carelessly, incomplete result, selfishnessand despair. Thus the nondichotomousreligious education and science in line with thebasic principles of the theological-dogmatic and philosophical-methodological